A model-based approach of scatter dose contributions and efficiency of apron shielding for radiation protection in CT. Issue 8 (December 2015) - Weber, N.; Monnin, P.; Elandoy, C.; Ding, S.
Abstract: Given the contribution of scattered radiations to patient dose in CT, apron shielding is often used for radiation protection. In this study the efficiency of apron was assessed with a model-based approach of the contributions of the four scatter sources in CT, i.e. external scattered radiations from the tube and table, internal scatter from the patient and backscatter from the shielding. For this purpose, CTDI phantoms filled with thermoluminescent dosimeters were scanned without apron, and then with an apron at 0, 2.5 and 5 cm from the primary field. Scatter from the tube was measured separately in air. The scatter contributions were separated and mathematically modelled. The protective efficiency of the apron was low, only 1.5% in scatter dose reduction on average. The apron at 0 cm from the beam lowered the dose by 7.5% at the phantom bottom but increased the dose by 2% at the top (backscatter) and did not affect the centre. When the apron was placed at 2.5 or 5 cm, the results were intermediate to the one obtained with the shielding at 0 cm and without shielding. The apron effectiveness is finally limited to the small fraction of external scattered radiation. Highlights: Our model-based approach showed a scattered dose reduction of only 1.5% on average. The apron at 0 cm from the beam lowered the dose by 7.5% at the phantom bottom. The apron increased dose by 2% at the top of the phantom (backscatter). The apron did not modify dose at the centre of the phantom. When the apron was placed at 2.5 or 5 cm from the beam, its effectiveness was lower.